The Role of Emotion in Elimination of Contribution and Collaboration Dilemma in Citarum River Basin Problem - Putro, Utomo Sarjono; Siallagan, Manahan; Novani, Santi; Utomo, Dhanan Sarwo (Jurnal Manajemen Teknologi, 2009)
The purposes of the current research are to identify, analyze and simulate the dynamics of interaction and conflicts among agents using drama theory in Citarum river basin problem. To accomplish these purposes, we crate a simulation model that combine drama theory and emotional state model (PAD model). Drama theory was adopted because it able to describe dilemmas and paradox arising from rational goal seeking behavior. It also provides us with rigorous analytical and computational tools for conflict analysis. Our previous model was able to recognize and solve confrontation dilemmas, i.e., persuasion and rejection dilemma among the agents. In this paper, we propose an enhanced simulation model that is able to recognize and solve collaboration dilemmas (trust dilemma) among the agents. In order to obtain some fruitful suggestions for encouraging agent’s collaboration, we product agent-based simulation using SOARS (Spot Oriented Agent Role Simulator).Keywords: Agent based Simulation, Negotiation, Dilemma, Drama Theory, Emotion